Sastra Arab dan Disabilitas: Pendekatan Ekspresif terhadap Puisi “al-Marsiyyah” Karya al-Ma’arri - Tatik Mariyatut Tasnimah (PLD UIN Sunan Kalijaga, 2019)
Surrounding factors, both the internal and external, always have a significant impact on a literary work. The most considerable external factor on literary works is the author himself, especially if he/she experiences a physical disorder with psychological implications. Such conditions can certainly give characteristics to the literary work. Al-Ma‘arri, who since his childhood suffered blindness, grew up to be a pessimistic person, always feeling isolated. This sadness led to deep contemplation of life, expressed in the poem